Herbicidal safening activity of Loropetalum chinense extract in alleviating pretilachlor-induced phytotoxicity in rice - Chen, Hongjun; Tang, Xing; Xiao, Long; Liu, Xiu; Jin, Chenzhong (Frontiers in Plant Science, 2026)
In this study, the crude extract of natural Loropetalum chinense (LoE) was prepared using a simple ethanol leaching approach. Preliminary evaluations of the safening effect of LoE in both agar and soil media demonstrated its ability to protect rice seedlings from damage induced by the herbicide pretilachlor (Pre). Specifically, treatment with LoE at 50 mg/L resulted in a 40.35% increase in root length and a 25.11% increase in plant height. In contrast, treatment at 100 mg/L led to a 36.85% increase in fresh weight, demonstrating effectiveness comparable to that of the commercial safener fenclorim (Fen). Moreover, compared to rice seedlings treated with Pre alone, LoE significantly increased the levels of glutathione (GSH) and enhanced the activities of several important enzymes: glutathione S-transferase (GST), superoxide dismutase (SOD), and catalase (CAT). The mechanism of action for LoE appears to involve enhancing GST activity to accelerate the metabolism of Pre and improving herbicide tolerance by activating antioxidant enzymes. Overall, LoE shows promise as a potential eco-friendly, plant-derived herbicide safener candidate for pretilachlor. For practical commercial application, further efforts should focus on (i) clarifying the phytochemical profile of LoE extracts, and (ii) conducting in-depth assessments of LoE’s mechanisms of action, including studies on degradation kinetics and metabolite formation.